1997
DOI: 10.1023/a:1010264717346
|View full text |Cite
|
Sign up to set email alerts
|

On the Adiabatic Expansion of the Visible Space in a Higher-Dimensional Cosmology

Abstract: In the context of higher-dimensional cosmologies we study the conditions under which adiabatic expansion of the visible external space is possible, when a time-dependent internal space is present. The analysis is based on a reinterpretation of the four-dimensional stress-energy tensor in the presence of the extra dimensions. This modifies the usual adiabatic energy conservation laws for the visible Universe, leading to a new type of cosmological evolution which includes large-scale entropy production in four d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Thus, the external space is radiation-dominated, while the internal one is pressureless. It has been recently shown that, in this case, the two subspaces are completely disjoint 4,31 . The time-evolution of the total mass-energy density ρ is accordingly given by Eq.(2.7).…”
Section: Numerical Resultsmentioning
confidence: 98%
“…Thus, the external space is radiation-dominated, while the internal one is pressureless. It has been recently shown that, in this case, the two subspaces are completely disjoint 4,31 . The time-evolution of the total mass-energy density ρ is accordingly given by Eq.(2.7).…”
Section: Numerical Resultsmentioning
confidence: 98%
“…In this context, q/c 2 represents a conversion constant between the gravitational and the electromagnetic field. The 5D field equations imply that A μ (i.e., N μ ) satisfy Maxwell-type equations [8][9][10].…”
Section: Five-dimensional Space-timementioning
confidence: 99%
“…First, studies of field equations (e.g., see [8][9][10]) and geodesic motion [6,8] claimed that the existence of extra dimensions manifests as new physics in ordinary 4D spacetime. The relationship between geodesic motion and the classical tests of general relativity adapted for 5D space-times may be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the metric ( 6) is an exact solution of the classical gravitational field equations when the pressure of the internal (one-dimensional) space equals to zero (p int = 0). According to Kleidis and Papadopoulos (1997a), as regards the thermodynamical description of two subspaces (the external space and the internal one), this condition corresponds to an adiabaticity criterion and therefore, no radiation (massless particles) is allowed to be transfered from one space to the other. Both subspaces represent closed thermodynamical systems (see also Prigogine et al 1989).…”
Section: Renormalizability Criteriamentioning
confidence: 99%